2014
DOI: 10.1002/jor.22581
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of surgical site infections after primary total joint arthroplasties

Abstract: We sought to characterize the causative pathogens of surgical site infections (SSIs) following primary total joint arthroplasties and to evaluate trends in the microbial etiology. We analyzed the etiology of SSIs following 2,632 total hip arthroplasty and knee arthroplasty procedures performed at our institution from 2004 through 2010. We calculated the annual proportion of SSIs accounted for each of the most common organisms and evaluated trends using the x 2 test for trend. SSIs were identified in 111 proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 22 publications
1
29
0
1
Order By: Relevance
“…In addition to Staphylococcus , many PJI‐causing bacteria can form biofilms, which are particularly resistant to treatments because they often require genus‐specific modes of eradication . Although biofilm structures vary, multiple species can coexist within one biofilm, which facilitates conjugation and could confer antibiotic resistance .…”
Section: Etiology Of Prosthetic Joint Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Staphylococcus , many PJI‐causing bacteria can form biofilms, which are particularly resistant to treatments because they often require genus‐specific modes of eradication . Although biofilm structures vary, multiple species can coexist within one biofilm, which facilitates conjugation and could confer antibiotic resistance .…”
Section: Etiology Of Prosthetic Joint Infectionsmentioning
confidence: 99%
“…Among PJIs, polymicrobial infections occur in approximately, 7–17% of cases overall (Table ) and are often most difficult to treat. Strikingly, though, Benito et al reported a fivefold increase in the yearly occurrence of polymicrobial infections from 7.1 to 41.7% over a period of 6 years from 2004 to 2010, and an equally alarming increase in the yearly proportion of infections caused by gram‐negative bacteria (21.4–66.7% over the same period). Of these, Enterobacteriaceae are challenging because they resist a wide range of antibiotics .…”
Section: Etiology Of Prosthetic Joint Infectionsmentioning
confidence: 99%
“…Importantly, the prevalence of methicillin-resistant S. aureus (MRSA) in PJI is increasing, especially in the USA [12]. In addition, polymicrobial infections can occur in up to 15% of cases [13] despite the fact that some authors reported a substantial increase in the yearly occurrence of polymicrobial infections over the period of six years (2004 to 2010) with a greater increase in the proportion of gram-negative bacteria during the same period [14]. …”
Section: Introductionmentioning
confidence: 99%
“…A single-centre study from France reported a small change in Enterobacteriaceae as causative pathogens in osteoarticular infections from 13% in 2002 to 15% in 2011 [20]. A further single-site study from Spain based on primary total joint arthroplasties reported a nonsignificant but marked increase in Gram-negative infections, from 21% in 2004 to 67% in 2010 [21].…”
Section: Key Pointsmentioning
confidence: 91%